Investigating the physiological response and antibody concentration of gilthead sea bream (Sparus aurata) following Vibrio anguillarum vaccination depending on the stress coping style - Carbonara, Pierluigi; Alfonso, Sebastien; Zupa, Walter; Manfrin, Amedeo; Fiocchi, Eleonora; Buratin, Alessandra; Bertazzo, Valentina; Cammarata, Matteo; Spedicato, Maria Teresa; Lembo, Giuseppe (Frontiers in Animal Science, 2022)
Stress coping styles (SCSs) are defined as coherent sets of individual physiological and behavioral differences in stress response consistent across time and context and are described in wide range of taxa, including fishes. These differences in behavior and physiology are of a great interest because they may have direct implications on animal health, welfare and performance in farming systems, including aquaculture. In this study, the physiological responses of sea bream (Sparus aurata) from different SCSs following Vibrio anguillarum vaccination have beenwere monitored. Fish were first screened either bold or shy (proxy of proactive and reactive SCS respectively) using group risk-taking tests, and were then injected with a vaccine against Vibrio anguillarum. Following vaccination, the fish were implanted with accelerometer tag to monitor the swimming activity (proxy of energy expenditure), and blood sampling has beenwas carried out to measure health and welfare parameters (e.g., cortisol, glucose, hemoglobin), aspecific immunity (e.g., protease, total proteins). In addition, blood was also collected at three different sampling times to screen antibodies level and thus to evaluate the efficiency of vaccine. Following vaccination, bold fish displayed lower swimming activity values, indicative of lower energy expenditure, while displayed higher level of hematocrit, total proteins and lysozyme in plasma than shy ones, which could be indicative of better health/welfare status and greater aspecific immunity. Finally, the Vibrio anguillarum vaccination appeared to be more efficient in bold fish since the number of total antibodies was found higher than in shy fish, one month after vaccination. These Such results could help to improve both health/welfare and productivity of farmed sea breams by selective more robust fish, better adapted to farming conditions.